Female, grief and Romanticism: a reflexive art history approach to a widow sculpture - Brites, Joana; Barbosa-Ribeiro, Marta (Arte, Individuo y Sociedad, 2019)
This paper aims to reflexively tackle a specific artwork: The Widow, the most renowned, yet under-studied, sculpture of António Teixeira Lopes, a prominent artist of the Portuguese nineteenth century. Therefore, the analysis of this piece, based on several inquiring procedures believed useful to all art historians, is converted into an epistemological exercise. Firstly, the Romantic sensibility is characterised, alongside the ponderment of the widow’s representational allure. Women and death’s perception in the nineteenth century is thus brought into question. Moreover, the social condition of widows and their identity codification is considered so that the relationship between reality and representation is critically appraised. Secondly, the focus shifts to the sculptor himself and his creative process. At the time living in Paris, his potential connections with death experiences, his professional goals and the pressure of the artistic environment contribute to explain Teixeira Lopes’ selection of this subject. Finally, the sculpture itself is thoroughly examined, questioning every formal choice and its meaning, searching for secular and contemporary visual stimuli which could have deliberately or unconsciously interacted within the creative process. To conclude, the need to approach an artwork simultaneously as unique and as a historical object in its turn chronologically transversal is stressed.